2000
DOI: 10.1159/000012128
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Surgical Treatment of Gastric Cancer Invading the Pancreas

Abstract: The clinicopathologic characteristics of gastric cancer invading the pancreas have not been determined. Gastrectomy was performed in 282 patients with gastric cancer invading adjacent organs at the Department of Surgery II, Kyushu University Hospital, between 1970 and 1987, and patient data were retrospectively analyzed using univariate and multivariate analyses. Of these patients, 150 (53.2%) had tumors invading the pancreas and 132 had tumors invading adjacent organs other than the pancreas. In both groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
6
18
0
1
Order By: Relevance
“…Such patients, theoretically, could have avoided this procedure; however, inconsistency between macroscopic and microscopic findings of infiltration has been reported to be 30%-50%, often because of inflammatory reactions surrounding the tumor [8,12]. Even if the latest diagnostic modalities, such as computed tomography (CT), magnetic resonance imaging (MRI), and endoscopic ultrasound (EUS) are used, it is very difficult to distinguish between inflammatory reactions and tumor infiltration before operation.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients, theoretically, could have avoided this procedure; however, inconsistency between macroscopic and microscopic findings of infiltration has been reported to be 30%-50%, often because of inflammatory reactions surrounding the tumor [8,12]. Even if the latest diagnostic modalities, such as computed tomography (CT), magnetic resonance imaging (MRI), and endoscopic ultrasound (EUS) are used, it is very difficult to distinguish between inflammatory reactions and tumor infiltration before operation.…”
Section: Discussionmentioning
confidence: 99%
“…The intraductal invaded cancer cells grew and finally packed the pancreatic duct. Maehara et al [7] classified pancreatic invasion of gastric cancer into three types: invasion only to the pancreatic capsule, invasion to the capsule and interlobular tissues, and invasion to the capsule and intralobular tissues. It has been reported that the degree of serosal invasion and lymphovascular invasion may be associated with locoregional recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, indications for splenectomy and Significance corresponds to the noted superscripts AL anastomotic leakage, N number, NR not reported, NS not significant, PD pancreaticoduodenectomy, PF pancreatic fistula, PP pancreaspreserving, PR pancreaticosplenectomy, pts patients, R0 resection with no residual tumor, SP spleen-preserving, SR splenectomy pancreatectomy in several of the articles included both extended lymphadenectomy and direct invasion [16,17,37,41,43,47,48]. Margin status is a strong prognostic indicator in patients undergoing surgery for gastric cancer, and positive margins are associated with decreased survival [14,42,45]. Accordingly, resections of the spleen and/or Significance corresponds to the noted superscripts AL anastomotic leakage, CG conventional gastrectomy, CL chylous leak, met presence of metastasis, MS median survival, N number, NR not reported, NS not significant, PF pancreatic fistula, PP pancreas-preserving, PR pancreaticosplenectomy, pts patients, R0 resection with no residual tumor, SP spleen-preserving, SR splenectomy pancreas in cases where direct invasion is suspected, in the absence of metastatic disease, may be treated with multivisceral resection [12,14,19,42,43,45], though some argue that survival may not be improved with an aggressive surgical approach [21].…”
Section: Discussionmentioning
confidence: 99%
“…Margin status is a strong prognostic indicator in patients undergoing surgery for gastric cancer, and positive margins are associated with decreased survival [14,42,45]. Accordingly, resections of the spleen and/or Significance corresponds to the noted superscripts AL anastomotic leakage, CG conventional gastrectomy, CL chylous leak, met presence of metastasis, MS median survival, N number, NR not reported, NS not significant, PF pancreatic fistula, PP pancreas-preserving, PR pancreaticosplenectomy, pts patients, R0 resection with no residual tumor, SP spleen-preserving, SR splenectomy pancreas in cases where direct invasion is suspected, in the absence of metastatic disease, may be treated with multivisceral resection [12,14,19,42,43,45], though some argue that survival may not be improved with an aggressive surgical approach [21]. Importantly, it is clear that resection of the spleen and pancreas for direct invasion should be considered separately from extended lymphadenectomy with spleen and pancreas preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation